PERMASALAHAN SERTA SOLUSI DALAM PENGHIMPUNAN DAN PENYALURAN DANA ZIS DI LAZISMU KOTA MEDAN - Ahmad Fuadi Tanjung; Yenni Samri Juliati Nasution (Sekolah Tinggi Pariwisata Mataram, 2022)
This research was carried out with the aim of knowing what problems and solutions this institution faced when collecting and distributing the ZIS funds. The subject of this research is the head of the fundraising division in the city of Medan. This study uses a descriptive type of research using qualitative data. The validity of this hypothesis uses observational techniques that are used to strengthen the problems in this study. The results of this study can be concluded that there is still a lack of public knowledge of this institution. Then, there are still people who distribute their zakat funds individually. This has become a problem in the collection and distribution of ZIS funds. there is still a lack of public knowledge of this institution. Then, there are still people who distribute their zakat funds individually. This has become a problem in the collection and distribution of ZIS funds. This study has limitations, among others, researchers cannot reach all respondents because they have separate sections and are busy with each other. These limitations are expected to be a lesson for researchers and can be avoided by further research